2013
DOI: 10.1007/s11999-013-2806-0
|View full text |Cite
|
Sign up to set email alerts
|

Skin Crease ‘Bikini’ Incision for Anterior Approach Total Hip Arthroplasty: Surgical Technique and Preliminary Results

Abstract: Background The direct anterior approach for THA allows implantation through an internervous plane without muscle detachment from bone. However, the classic longitudinal skin incision does not follow the anatomic skin creases and can result in scar widening. We therefore modified our incision technique to a short oblique skin incision following the anatomic skin crease of the groin.Questions/purposes We sought to determine whether (1) the oblique incision leads to improved scar results compared with the longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 17 publications
(17 reference statements)
2
78
0
Order By: Relevance
“…In most studies reporting a lower incidence rate around 10 %, the injury of LFCN was defined as numbness and/or burning sensation on the anterolateral thigh at outpatient visit [13,18]; however, those evaluations might be underreporting LFCN injury because of low sensitivity [12]. In contrast, some studies reported a higher incidence rate up to 67 % by conducting evaluation with greater awareness of this specific complication [12,19]. For example, Krista et al investigated the incidence of LFCN injury in 132 patients after DAA for THA with an average follow up of 13.4 months [12].…”
Section: Discussionmentioning
confidence: 99%
“…In most studies reporting a lower incidence rate around 10 %, the injury of LFCN was defined as numbness and/or burning sensation on the anterolateral thigh at outpatient visit [13,18]; however, those evaluations might be underreporting LFCN injury because of low sensitivity [12]. In contrast, some studies reported a higher incidence rate up to 67 % by conducting evaluation with greater awareness of this specific complication [12,19]. For example, Krista et al investigated the incidence of LFCN injury in 132 patients after DAA for THA with an average follow up of 13.4 months [12].…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of injury of the LFCN with the anterior approach varies considerably, from 0.1% to 81% [15][16][17]37,38 . This variation may be explained by different interpretations or lack of recognition of LFCN injury, or the diversity of skin incisions chosen for the anterior approach 2,16,33,34,38 . While some authors observed that most symptoms of LFCN paresthesia resolved after 6 to 24 months 12 , others reported only a small number of patients with complete resolution 13 .…”
Section: Course O F T H E Lat E R a L Femoral Cutaneous N E Rv E W I mentioning
confidence: 99%
“…The 'Bikini incision' suggested by Delany and Carnevale 5 was designed to allow the use of brief bathing suits, but those suits were dimensionally different four decades ago as compared to those used nowadays. Furthermore, the 'Bikini line' described by Leunig et al 9 defined a line more restricted and slightly more inferiorly placed than those reported by Vaidya et al 8 . Consequently, we notice the variability of this term's interpretation.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, Vaidya et al 8 investigated clinically and anatomically the 'Bikini area' and 'Bikini line' (connecting the anterior inferior iliac spines) as a location for anterior subcutaneous pelvic fixation. Even more recently, Leunig et al 9 reported the use of skin crease 'Bikini' incision for anterior approach total hip arthroplasty.…”
Section: All Authors Contributed To the Conception Design And Prepamentioning
confidence: 99%